PERANCANGAN ANTARMUKA ONLINE COURSE PADA PERANGKAT MOBILE MENGGUNAKAN TEORI USABILITY - Elia Zakharia; Djoko Budiyanto Setyohadi; Y. Sigit Purnomo W. P. (Universitas Kristen Duta Wacana, 2016)
E-learning model can be developed into various forms according to the context of development. All of e-learning model aims to support learning process. The main objective of this study was to design online course interface that runs in mobile device using the theory of usability ISO 9241-11 in UAJY (Universitas Atma Jaya Yogyakarta). Data was collected from 55 undergraduate students of UAJY. It is used as initial state in design process. Furthermore, online course interface design created with use case diagram that adapted to activities of HTA. Nevertheless, in the design process components of interface created by the user persona and mobile device pattern, as well as guided by MGQM, which is also adapted to the limitations of this study and the conditions in UAJY. In addition, using log data collection to handle part of MGQM, which related with time, steps, resources.